IL-23, not IL-12, Directs Autoimmunity to the Goodpasture Antigen - Ooi, Joshua D. (American Society of Nephrology, 2009)
The autoantigen in Goodpasture disease is the noncollagenous domain of α3 type IV collagen [α3(IV)NC1]. We previously demonstrated that IL-12p40(−/−) mice are protected from experimental autoimmune anti–glomerular basement membrane (anti-GBM) glomerulonephritis, seemingly defining a role for IL-12 in this disease; however, the recent identification of IL-23, a heterodimer composed of IL-12p40 and IL-23p19 subunits, raises the possibility that IL-23, rather than IL-12, may modulate this disease instead. We immunized wild-type, IL-12p35(−/−) (IL-12 deficient, IL-23 intact), IL-12p40(−/−) (deficient in both IL-12 and IL-23), and IL-23p19(−/−) (IL-12 intact, IL-23 deficient) mice with recombinant mouse α3(IV)NC1. Wild-type mice developed autoreactivity to α3(IV)NC1: Humoral responses, cellular responses, renal histologic abnormalities, leukocyte accumulation, autoantibody deposition, and IL-17A mRNA expression (a cytokine produced by the IL-23–maintained Th17 subset). IL-23 but not IL-12 was detected in the immune system. Regardless of the presence of IL-12, mice deficient in IL-23 were protected, but mice with IL-23 were not. Both IL-23–deficient strains exhibited lower autoantibody titers, reduced cellular reactivity, diminished cytokine production (IFN-γ [Th1], IL-17A [Th17], TNF, and monocyte chemoattractant protein 1), and less renal disease and glomerular IgG deposition. The deficient responses in the absence of IL-23 were not due to increased regulatory T cells; IL-12p40(−/−) and IL-23p19(−/−) mice did not show increased proportions of CD4(+)CD25(+)FoxP3(+) cells or IL-10 levels early in the immune response. In conclusion, autoreactivity to the Goodpasture antigen is directed primarily by IL-23, absence of which results in hyporeactivity including but extending beyond a deficient Th17 response.